Analisis Harga Saham dan Return Saham Pada Anak Perusahaan PT Indonesia Asahan Aluminium Sebelum dan Sesudah Akuisisi PT Freeport Indonesia - Stephen Richard Reynaldi Putra Nober; Veny Anindya Puspitasari (Jurnal Pasar Modal dan Bisnis, 2020)
The purpose of this research is to analyze the differences in stock prices and stock returns before and after the acquisition of PT Freeport Indonesia by PT Indonesia Asahan Alumunium. This type of research is an event study with a period of three months before the acquisition and three months after the acquisition. The research subjects used in this study are companies that are part of the Holding BUMN Mining PT Indonesia Asaham Alumunium (MIND ID) which has become a public company and is listed on the Indonesia Stock Exchange, namely PT Aneka Tambang Tbk., PT Timah Tbk., And PT Bukit Asam Tbk. The test tool used to analyze the differences in stock prices and stock returns before and after the acquisition is the Paired Sample T-Test. The results showed that there were significant differences in the stock prices of PT Aneka Tambang (ANTM), PT Bukit Asam Tbk (PTBA), and PT Timah Tbk (TINS) but there was no significant difference in the stock returns of the three companies.